Purβ promotes hepatic glucose production by increasing Adcy6 transcription - Linna Jia; Yunfeng Jiang; Xinzhi Li; Zheng Chen (Elsevier, 2020)
Objective: Enhanced glucagon signaling and hepatic glucose production (HGP) can account for hyperglycemia in patients with obesity and type 2 diabetes. However, the detailed molecular mechanisms underlying the enhanced HGP in these patients are not fully understood. Here, we identify Purβ as a positive regulator of HGP and study its molecular mechanisms in the regulation of HGP both in vivo and in vitro. Methods: Adenovirus-mediated knockdown or overexpression of Purβ was performed in either primary hepatocytes or the livers of db/db mice. Glucose metabolism, insulin sensitivity, and HGP were determined by glucose, insulin, and lactate tolerance tests, respectively. Purβ/ADCY6 protein levels, glucagon signaling (p-CREB/CREB), and insulin signaling (p-Akt/Akt) were measured by immunoblotting. Gene expression was measured by RNA-seq and real-time quantitative polymerase chain reaction. Luciferase reporter and chromatin immunoprecipitation assays were used to study the interaction between Purβ and the Adcy6 promoter. Results: Purβ was abnormally elevated in obese mice and was also increased under fasting conditions or via the glucagon signaling pathway, which promoted HGP by increasing Adcy6 expression. Liver-specific knockdown of Purβ in db/db mice significantly ameliorated hyperglycemia and glucose intolerance by suppressing the glucagon/ADCY6/cAMP/PKA/CREB signaling pathway. Consistent with this observation, the knockdown of Purβ also inhibited glucose production in isolated primary hepatocytes by inhibiting the glucagon/ADCY6/cAMP/PKA/CREB signaling pathway, whereas the overexpression of Purβ promoted glucose production by activating this signaling pathway. Mechanistically, Purβ directly binds to the promoter of the Adcy6 gene and thereby promotes its transcription. Conclusions: Taken together, these results illustrate a new model in which Purβ functions to regulate the glucagon/ADCY6/cAMP/PKA/CREB signaling pathway to help maintain glucose homeostasis. Keywords: Purβ, Liver, Gluconeogenesis, Glucagon signaling, ADCY6, Obesity